Pleasant for some and unpleasant for others: a protocol analysis of the cognitive factors that influence affective responses to exercise - Parfitt Gaynor; Rose Elaine A (BMC, 2010)
Abstract Background At exercise intensities around ventilatory threshold (VT), the extent to which individuals experience pleasure or displeasure from the exercise varies between individuals. One source of this variability is proposed to be the cognitive appraisal that occurs during the exercise which influences the generation of the affective response. When individuals self-select their own intensity they choose to exercise around VT and experience more positive affective responses, again the explanation being that cognitive appraisal processes influence the choice of intensity and resulting affective response. However, the specific factors that comprise this appraisal process have not been thoroughly explored. In addition, it is not clear if activity status influences this appraisal and different cognitive factors play a role in the generation of affective responses. Therefore, the purpose of this study was to explore the cognitive factors that influence the affective response experienced during prescribed and self-selected intensity exercise in low-active and high-active women. Methods Seventeen low-active and 15 high-active women (M age = 45 years, SD = 10) completed a graded exercise test and two 30 min bouts of treadmill exercise, one at a self-selected intensity and one prescribed at an intensity around VT. Using 'think aloud' procedures, every five min, the women were asked to provide an affective response and explain the thought processes that caused them to report that affective response. Using inductive content analysis, the verbal reports provided by the women were analysed for key themes and categories that emerged as explaining the factors that underpinned the generation of the affective response. Data from the low-active and high-active women were analysed separately. Results Concepts relating to pre-exercise affective state, perceptions of ability, immediate and anticipated outcomes, attentional focus and perceptions of control emerged. The physiological demands of the exercise stimulus influenced affective responses through themes related to the interpretation of physiological symptoms and the physiological state of the body. No thematic differences emerged between high-active and low-active women. Conclusion Results highlight the complex interaction of psychological and physiological influences in producing an affective response to exercise and provide insight into how exercise can be structured to elicit positive affective responses.